Prostitution, condom use, and invasive squamous cell cervical cancer in Thailand - David B. Thomas (2018)
Cervical cancer is probably caused by a sexually transmitted agent. A case-control study was conducted in three hospitals in Thailand to investigate further the role of male sexual behavior, particularly regarding sexual contacts with prostitutes, in the development of this disease. Data were obtained from interviews with 225 married women with invasive squamous cell cervical carcinoma and 791 hospitalized controls, all of whom reported having only one sexual partner, and from interviews with their husbands. Risk of cervical cancer was strongly related to the women's husbands having visited prostitutes without using a condom when the husbands were less than 30 years old. A strong increasing trend in risk in relation to decreasing frequency of the husbands' condom use with prostitutes was observed, and a weaker increasing trend in risk with husbands' estimated lifetime total number of visits to prostitutes was found. The average latent period between the women's likely initial exposure to a sexually transmitted oncogenic agent and her diagnosis of invasive cervical cancer was about a quarter of a century. Regular use of condoms by customers of prostitutes could reduce the number of invasive cervical cancer cases in the general population of Thailand by at least one fourth.